Phase 1/2 trial of GCLAM with dose-escalated mitoxantrone for newly diagnosed AML or other high-grade myeloid neoplasms. Issue 11 (November 2018) - Halpern, Anna; Othus, Megan; Huebner, Emily; Scott, Bart; Becker, Pamela; Percival, Mary-Elizabeth; Hendrie, Paul; Gardner, Kelda; Chen, Tara; Buckley, Sarah; Orlowski, Kaysey; Anwar, Asma; et al.
Abstract Outcomes with "7 + 3" are often unsatisfactory in acute myeloid leukemia (AML). Trials demonstrating improved outcomes with high-dose cytarabine, addition of cladribine, or escalated anthracycline doses prompted a phase 1/2 study (NCT02044796) of G-CSF, cladribine, high-dose cytarabine, and dose-escalated mitoxantrone (GCLAM) in adults with newly-diagnosed AML or other high-grade myeloid neoplasms. One hundred and twenty-one patients, median age 60 (range 21–81) years, were enrolled. In phase 1, cohorts of 6–12 patients were assigned to 12–18 mg/m2 /day of mitoxantrone as part of GCLAM. Because all dose levels were well-tolerated, mitoxantrone at 18 mg/m2 was declared the recommended phase 2 dose (RP2D). 74/94 (79%) patients treated at the RP2D achieved a complete remission (CR; 67/74 without measureable residual disease [MRD]) for an overall MRDneg CR rate of 71% (primary phase 2 endpoint). Seven patients achieved a CR with incomplete blood count recovery (CRi; 7%, 5 MRDneg ) for a CR/CRi rate of 81/94 (86%). Four-week mortality was 2%. After adjustment, the MRDneg CR and CR/CRi rates compared favorably to 100 matched controls treated with 7 + 3 at our center and 245 matched patients treated with 7 + 3 on a cooperative group trial. Our data indicate GCLAM with mitoxantrone at 18 mg/m2 /day is safe and induces high-quality remissions in adults with newly-diagnosed AML.